2008
DOI: 10.1590/s0080-62342008000100002
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade do sono em pacientes idosos com patologias vasculares periféricas

Abstract: Patologias vasculares periféricas freqüentemente acometem idosos e, sendo crônicas, interferem na qualidade de vida desses indivíduos, inclusive no sono. Portanto, este estudo objetivou avaliar a qualidade do sono de idosos com patologias vasculares periféricas em acompanhamento ambulatorial no Hospital das Clínicas da Universidade Estadual de Campinas. Os voluntários (n=50, idade média de 74 8 anos) responderam ao Índice de Qualidade de Sono de Pittsburgh (PSQI), forneceram dados sociodemográficos e sobre a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 14 publications
0
10
0
10
Order By: Relevance
“…In a similar study (8) , pain complaints were reported by 33% of the elderly. Pain is a recognized factor of nocturnal sleep disorder, generally more prevalent in the elderly, and associated to reflexes in performance during wakefulness (12) .…”
Section: Evaluation Of Sleep Quality and Its Componentsmentioning
confidence: 99%
“…In a similar study (8) , pain complaints were reported by 33% of the elderly. Pain is a recognized factor of nocturnal sleep disorder, generally more prevalent in the elderly, and associated to reflexes in performance during wakefulness (12) .…”
Section: Evaluation Of Sleep Quality and Its Componentsmentioning
confidence: 99%
“…The univariate logistic regression analysis showed several factors associated with symptoms of insomnia in the interviewees, such as: being female, living alone or with the family, not being retired, report of urinary incontinence, rheumatoid arthritis, depression and a health self-evaluation rated as good, fair, poor or very poor. Most of these factors, such as being female (4)(5) , urinary incontinence (7)(8) and (7)(8) , have traditionally been associated with complaints of this nature.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of sleep-disordered breathing and disorders related to increased nocturnal myoclonic activity are also more common over 60 years of age, so that the complaints of insomnia symptoms are most frequent among the elderly (4)(5) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adicionalmente, períodos mais curtos de sono foram associados à angina, enquanto períodos curtos e longos foram associados ao infarto agudo do miocárdio e acidente vascular cerebral. 29,30 Com relação a qualidade do sono, no presente estudo foi verificado que 38,6% dos participantes avaliados apresentaram qualidade do sono ruim, resultado inferior ao de outras pesquisas, [31][32][33] algo que pode ser explicado em parte devido aos pacientes estarem participando de um programa de reabilitação cardiopulmonar e metabólica, que tem como objetivo a adoção de um estilo de vida mais saudável associado à prática regular de exercício físico, que pode ser explicado devido aos pacientes possuírem doenças crônicas cardíacas e metabólicas.…”
Section: Estado Nutricionalunclassified